Adolescents' Perceptions of Substance Use Harms are Contingent on Mode of Administration and Type of Substance. (August 2022) - Cummins, Kevin; Lu, Yang
Early vaping research often did not differentiate between substances vaped. The present study investigates risk perceptions for vaped nicotine and vaped cannabis. A school-based census of 9th and 11th graders yielded 431 responses to the California Healthy Kids Survey. Differences in harm perceptions were evaluated using multilevel mixed-effects models. Students were more likely to report nicotine vaping as great-moderate risk in comparison to cannabis vaping. Additionally, vaped cannabis was viewed as riskier than traditional administration. These results indicate that differences in harm perceptions may need to be addressed when targeting specific classes of substance use in investigations and interventions.